1993
DOI: 10.1121/1.405653
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation pressure acting on spherical and cylindrical shells

Abstract: The acoustic radiation pressure resulting from a plane wave incident on spherical shells and cylindrical shells immersed in a fluid is investigated theoretically in relation to the thickness of the shell and the contents of the hollow region. The results for the frequency dependence of acoustic radiation pressure computed on the basis of the theory are demonstrated for stainless shells with the hollow region filled water or air. Significant differences in acoustic radiation pressure occur when the interior reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 0 publications
1
59
0
1
Order By: Relevance
“…The acoustic radiation pressure resulting from a plane wave incident upon spherical and cylindrical shells was also studied by Hasegawa et al [28] and it was shown that the differences between the frequency dependence of acoustic radiation pressure on spherical and cylindrical shells are more pronounced than those between solid spheres and cylinders. Wei et al [29] calculated the acoustic radiation force on a compressible cylinder in a standing wave.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The acoustic radiation pressure resulting from a plane wave incident upon spherical and cylindrical shells was also studied by Hasegawa et al [28] and it was shown that the differences between the frequency dependence of acoustic radiation pressure on spherical and cylindrical shells are more pronounced than those between solid spheres and cylinders. Wei et al [29] calculated the acoustic radiation force on a compressible cylinder in a standing wave.…”
Section: Introductionmentioning
confidence: 99%
“…. It can now be readily shown that and the axial radiation force is given by the following well-known relation [26,28]:…”
Section: 〈∫ ( ) 〉 (14-4)mentioning
confidence: 99%
See 2 more Smart Citations
“…The radiation force is a function of all the parameters that affect the scattered wave. Some of these parameters are the size, shape, material properties, location, orientation and the internal structure of the object [1][2][3][4][5][6][7][8] . There are several theoretical analyses of the acoustic radiation force confirming its dependency on the mentioned parameters.…”
Section: Introductionmentioning
confidence: 99%